Information Technology Disaster Recovery Plan (IT-DRP) Model-Based on NIST Framework in Indonesia - Hanung Nindito Prasetyo; Nana Supriatna; Anugrah Pambudi Raharjo; Wawa Wikusna (IJAIT (International Journal of Applied Information Technology), 2020)
Based on data, Indonesia ranks second in the list of the highest number of deaths due to natural disasters in the Asia-Pacific. Over the past 20 years, various natural disasters in this country have also caused economic losses of at least US$ 22.5 billion. This data means that disasters in various sizes and scales can occur and affect business. Disaster threats can occur in various forms, such as earthquakes, tsunamis, and floods. The threat of disasters will certainly disrupt and can have a fatal impact on the sustainability of business supported by information technology, the Ministry of Women's Empowerment and Child Protection (KPPPA) as a case study has an interest in this matter. One of the infrastructures that become an essential asset as the performance support capacity of the KPPPA is an information system and technology. System tools and Information technology are business process support tools at the KPPPA so that businesses have sustainability and can run well. Disasters that occur will undoubtedly have a fundamental impact that can damage the system and technology in the organization so that it will positively affect the course of business processes. For this reason, integrated planning is needed to handle the disaster so that business processes can continue to run as they should. One of the integrated plans is designing an Information Technology and Communication Disaster Recovery Plan (IT-DRP). This study discusses the NIST framework implementation as one of the IT-DRP models which have been applied in KPPPA.